EXHAUST EMISSION CHARACTERISTICS OF A GARDENER COMPRESSION IGNITION ENGINE FUELLED WITH RAPESEED METHYL ESTER AND FOSSIL DIESEL (Nigerian Journal of Technology, 2020)
This paper presents an experimental investigation into the exhaust emissions characteristics of a gardener Compression Ignition (CI) Engine fuelled with rapeseed methyl Esther (RME) and fossil diesel under lean equivalence ratios (0.2? ? ?0.8).  The experiments were carried out at engine speeds of 750 and 1250 rpm under five different loads. The experimental results showed that NOx and CO2 emissions increased while emissions of HC, O2 and CO decreased with increasing equivalence ratio, exhaust temperature, brake mean effective pressure and specific fuel consumption. All exhaust emissions were found to decrease with increasing engine speed from 750 to 1250 rpm. There was reduction in exhaust emissions of RME over fossil diesel by 0.06% for O2, 84% for CO and 4.7% for CO2 at 750rpm. At higher speed of 1250rpm however, RME was observed having higher NOx and CO2 but relatively lower O2 and CO than the fossil diesel.  http://dx.doi.org/10.4314/njt.v39i3.14